2008
DOI: 10.1021/la8009892
|View full text |Cite
|
Sign up to set email alerts
|

Assembly of Nanozeolite Monolayers on the Gold Substrates of Piezoelectric Sensors

Abstract: Colloidal zeolites NaA (LTA structure type) and ZSM-5 (MFI-type) with crystal diameters of about 100 nm were synthesized as building blocks for the formation of microporous self-limiting monolayers on the piezo-active area (gold electrodes) of a quartz crystal microbalance (QCM). Two different coupling strategies were explored, concerning the modification of either the gold substrate or the external zeolite crystal surface with a bifunctional molecular interface. Diverse analytical methods were employed to ful… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 23 publications
1
13
0
Order By: Relevance
“…The XRD patterns of zeolites LTA and BEA (Fig. 1) indicated that the materials were obtained as pure crystalline phases [47,48,55]. The XRD data for the Nano-X/Na zeolite were also indicative of a pure zeolite with faujasite topology, without the presence of organic templates or structure-directing agents (SDAs) [49,56].…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…The XRD patterns of zeolites LTA and BEA (Fig. 1) indicated that the materials were obtained as pure crystalline phases [47,48,55]. The XRD data for the Nano-X/Na zeolite were also indicative of a pure zeolite with faujasite topology, without the presence of organic templates or structure-directing agents (SDAs) [49,56].…”
Section: Resultsmentioning
confidence: 97%
“…In a typical synthesis procedure, an aluminosilicate gel was prepared by mixing together freshly prepared aluminate and silicate solutions (or titanate and silicate solutions, in the case of TS1), following experimental procedures adapted from the literature [45][46][47][48][49]. The nanocrystals were cooled to room temperature and were then recovered by centrifugation (Hitachi Koki himac CR22N High-Speed Refrigerated Centrifuge), washed with deionized water until reaching pH <8, and dried at room temperature for 24 h. These samples were denoted U-Nano/TS1, U-Nano/GIS, U-Nano/LTA, U-Nano/BEA, and U-Nano-X (where U stands for unfunctionalized nanozeolite).…”
Section: Synthesis Of Nanozeolitesmentioning
confidence: 99%
“…In pioneering studies, Yoon et al and Biemmi and Bein proposed to improve the assembly of a zeolite film on a support by using 1,4-diisocyanate (DIC-4) as a molecular binder via the reaction of isocyanate groups with hydroxy groups. 42,43 However, to the best of our knowledge, there is still no report on the preparation of molecular sieve membranes by using diisocyanates as molecular linkers until now. In the present work, we adopt and develop this concept for in situ growth of dense supported zeolite membranes/ layers on DIC-4 functionalized supports, as shown in Fig.…”
Section: -39mentioning
confidence: 99%
“…However, the beneficial properties of the small definite pore openings cause diffusion limitations of larger reacting molecules, leading to restrictions in the catalyst activity and lifetime. To overcome this problem a lot of research has been done in the last years to shorten the diffusion length in zeolites, either by reducing the particle size [3,4] or by introducing an additional mesoporous transport network [5][6][7][8]. The introduction of such a network can be achieved by hardtemplating [5,9,10] or soft-templating [11][12][13] techniques.…”
Section: Introductionmentioning
confidence: 99%